The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s0963926817000025
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the West End: social science, mental health and the American urban environment, 1939–1968

Abstract: ABSTRACT:Analysing the urban renewal of Boston's West End during the 1950s, we examine how psychiatrists, social scientists and urban planners understood the relationship between the urban environment and mental health. For psychiatrist Erich Lindemann, the West End offered a unique opportunity to study how acute stress and loss affected populations, thus contributing to social psychiatry, which sought to prevent mental illness by addressing factors in the social and physical environment. While Lindemann's pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Such nuances, however, were often lost in the efforts to clear slums after World War II, as the research of Jane Jacobs (1961), Herbert Gans (1962), Erich Lindemann and others indicated (Ramsden and Smith, 2018). In 1958, for instance, the Boston Redevelopment Authority began demolishing a 48-acre section of Boston's West End that had been home to 2700 families, including a large number of lower-working-class Italian-Americans.…”
Section: Hobos and Ghetto Dwellersmentioning
confidence: 99%
“…Such nuances, however, were often lost in the efforts to clear slums after World War II, as the research of Jane Jacobs (1961), Herbert Gans (1962), Erich Lindemann and others indicated (Ramsden and Smith, 2018). In 1958, for instance, the Boston Redevelopment Authority began demolishing a 48-acre section of Boston's West End that had been home to 2700 families, including a large number of lower-working-class Italian-Americans.…”
Section: Hobos and Ghetto Dwellersmentioning
confidence: 99%
“…In the mid 20th century, the human sciences often attributed an individual's psychological state to larger societal forces; for example, psychoanalysis studied social and environmental forces, social psychiatry often focused on urban studies, and sociology developed an interest in other-directed personalities (Ramsden and Smith, 2018). In Company , Sondheim and Furth paralleled this attribution of problems to societal causes by using New York City as a central force in the show's narrative.…”
Section: ‘Alone Is Alone Not Alive’: the Lonely Crowd In Companymentioning
confidence: 99%
“…In the history of writing on the effects of modern metropolitan life on mental health, an influential line of thought with roots in urban sociology argues that the stresses and strains faced by vulnerable populations such as the urban poor, combined with challenging urban conditions such as overcrowding, and sensory overstimulation, make for mental disorders such as anxiety, stress, depression, and schizophrenia (see Fitzgerald et a., 2016a, 2016b; Ramsden & Smith, 2018). Simmel (1964/1919), for example, argued that urban hyperaesthesia threatens mental health, if not kept at bay by city dwellers, learning to adopt postures of inurement and indifference.…”
Section: Introductionmentioning
confidence: 99%